Functional microstructured surface polishing: mechanism and applications - Huang Li; Wenwen Lu; Junfeng Liu; Yifan Dai; Xiaoqiang Peng; Hao Hu; Chaoliang Guan; Chao Xu; Tao Lai; Fei Dong (Journal of Materials Research and Technology)
Functional microstructured surfaces are becoming increasingly important in the fields of optics, microfluidics, and surface engineering. These parts' functional surface roughnesses and microstructure molding accuracies directly affect their final service performance characteristics. To improve the machining qualities of functional microstructured surfaces, subsequent polishing treatment is necessary. This paper discusses the different polishing methods and effects of functional microstructured surface parts. Moreover, the challenges and bottlenecks in polishing functional microstructured surfaces are analyzed and discussed by considering the microstructure feature sizes, shapes, and substrate surface shapes. Then, the advantages, disadvantages, applications, and limitations of functional microstructured surface polishing methods are elucidated. Finally, the development trends of form-preserving polishing methods for functional microstructured surfaces are noted.